Improved calculations for no-load transformer switching surges. - Popov, M. (IEEE Transactions on power delivery)
This paper deals with a modeling of components and calculation of transient overvoltages that build up on the transformer primary terminals after the transformer has been switched off by a vacuum circuit breaker (VCB). The transformer is connected to the circuit breaker by a cable. The transient overvoltages are calculated for different cable lengths, and the cumulative probability of different arc angles is investigated. In this study two cases are considered: transient overvoltages due to steady-state magnetizing current switching, and transient overvoltages due to inrush current switching. It is shown that the case of inrush current switching is worse, as virtual current chopping is possible. The cable is modeled by pi sections, whereas the transformer model is based on a terminal impedance. The VCB re-ignitions are modeled by means of withstand voltage characteristics and high-frequency quenching capability. Due to shortage of field tests, this work uses only literature references to compare the results with actual measurements